Solid‐state synthesis of BaCe0.16Y0.04Fe0.8O3‐δ cathode for protonic ceramic fuel cells. Issue 4 (9th June 2022) - Shi, Huangang; Hu, Ying; Feng, Zixuan; Qu, Jifa; Yu, Yang; Zhang, Dongping; Tan, Wenyi
Abstract: Protonic ceramic fuel cells (PCFCs) are energy conversion devices based on proton conducting oxide electrolytes, which efficiently convert the chemical energy of fuel into electrical energy during operation. Since the conduction of protons has a lower activation energy than the conduction of oxygen ions, PCFCs can work at medium to low temperatures. In order to obtain better output performance at medium to low temperatures, the cathode of PCFCs needs to have better activity, and the triple (H + /O 2− /e − ) conducting oxide is a very good choice. In this study, the triple conducting BaCe0.16 Y0.04 Fe0.8 O3‐δ (BCYF) cathode material was synthesized by the traditional solid‐state reaction method, and the structure and morphology of the cathode material during the synthesis process were investigated. The results show that the powder synthesized by the solid‐state reaction method has a particle size comparable with that of the wet chemical method, and the as‐fabricated electrode exhibits a polarization resistance of 0.91 Ω cm 2 at 700°C on the Ba Zr0.1 Ce0.7 Y0.1 Yb0.1 O3‐δ (BZCYYb) electrolyte of 0.91 Ω cm 2 at 700°C. A fuel cell, using Ni‐BZCYYb anode, BZCYYb electrolyte, and BCYF cathode, achieves a maximum power density of 213 mW cm −2 at 600°C.